A facile synthesis of porous N-doped carbon with hybridization of Fe3C nanoparticle-encased CNTs for an advanced oxygen reduction reaction electrocatalyst. Issue 10 (5th September 2018) - Zhao, Pingping; Nie, Hanqiu; Yu, Jiahao; Wang, Jianbo; Cheng, Gongzhen
Abstract : Excellent ORR catalysis activity in both alkaline and acid media was found in porous N-doped carbon hybridized with Fe3 C nanoparticle-encased CNTs by annealing ZIF-8, FeC2 O4 and cyanoguanidine. Abstract : A facile synthesis of N-doped porous carbon hybridized with N-doped carbon nanotubes encapsulated with Fe3 C nanoparticles (FeNC-ZIF-800) by simply annealing a mixture of metal–organic frameworks (ZIF-8), FeC2 O4 and cyanoguanidine at 800 °C in Ar was designed. Carbon or a relatively high temperature could lead to a pure phase of Fe3 C. A certain ratio of these precursors and an appropriate carbonization temperature is crucial in the formation process of the special hierarchical structure; the addition of ZIF-8 can enhance the BET surface area and regulate the pore structure distribution to a large extent. The good conductivity, hierarchical struture and the synergistic effect between CNTs and carbon are considered to be the major reasons that result in their highly efficient performances toward the ORR. In 0.1 M KOH solution, the as-synthesized FeNC-ZIF-800 showed a half-wave potential of 0.86 V, ca. 40 mV more positive than that of 20% commercial Pt/C. In 0.5 M H2 SO4 solution, a good onset potential of nearly 0.85 V and a half-wave potential of 0.74 V can be achieved.